Demographische Effekte auf die zukünftigen Behandlungsausgaben und den zukünftigen Beitragssatz der GKV - Manfred Erbsland (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1995)
This paper analyses the pure demographic effect on medical expenditure and the contribution rate of the German Statutory Health Insurance Scheme. To isolate this effect, we assume that the age-specific expenditure for medical treatment as estimated in 1995 remains constant over the whole prediction period (1995 until 2040). The estimates show that ceteris paribus the double aging of the German population increases (average) per-capita medical expenditure about 20 percent. The corresponding increase in the (average) contribution rate sums up to approximately 3 percentage points.
Keywords: 330; Gesundheitsfinanzierung; Krankenversicherung; Sozialversicherungsbeitrag; Bevölkerungsentwicklung; Deutschland